Existing Evaluation and Efforts to Improve the Distribution Network of Banyuwangi District PDAM (Banyuwangi City Study Area) - Setyawan, Danang Budi; Karnaningroem, Nieke (Institut Teknologi Sepuluh Nopember, 2019)
The drinking water sector is the aspect of development that has a pivotal function to support the welfare of society. This is due to health, lifestyle, residential environment conditions and comfort in daily life. The service of the piped water supply system (SPAM-JP) for the service of the capital city of Banyuwangi Regency covers 5 Subdistricts, with 44% clean water service coverage, installed production capacity of 405 liters/second and operating 330 liters/second, to service 34,319 Connection Units with customers domestic (Household) as many as 32,271 units and non-domestic as many as 2,046 units of connection. In addition, the level of continuity has not yet been achieved, this can be seen in some service areas during peak hours not flowing, besides the level of water loss is 25%. In anticipating all problems in the service, research is conducted by analyzing the technical aspects, financial aspects, and institutional aspects. In analyzing each aspect, it was used the appropriate method and updated data. The technical aspects was done by calculating water balance uses easy calk, network analysis using epanet 2.0 and determining improvement efforts. In the institutional aspects was done by the assessment of BPSPAM, while the financial aspects by analyzing the investment costs of network improvements required and alternative funding. The evaluation of existing conditions is that the production and distribution units are not optimal, in the water balance the water loss is 25%, from the HR assessment there is no activity to improve the existing HR and efforts to improve the distribution network include general improvements in the form of pipe replacement and DMA formation in all service areas and managements, namely by increasing HR and developing computer-based information systems